Occurrence of fatal police violence during pregnancy and hazard of preterm birth in California. Issue 4 (10th March 2021) - Goin, Dana E.; Gomez, Anu Manchikanti; Farkas, Kriszta; Duarte, Catherine; Karasek, Deborah; Chambers, Brittany D.; Jackson, Andrea V.; Ahern, Jennifer
Abstract: Background: Exposure to fatal police violence may play a role in population‐level inequities in risk for preterm delivery. Objective: To evaluate whether exposure to fatal police violence during pregnancy affects the hazard of preterm delivery and whether associations differ by race/ethnicity and fetal sex. Methods: We leveraged temporal variation in incidents of fatal police violence within census tracts to assess whether occurrence of fatal police violence in a person's tract during pregnancy was associated with increased hazard of extremely (20‐27 weeks), early (28‐31 weeks), moderate (32‐33 weeks), and late (32‐36 weeks) preterm delivery in California from 2007 to 2015. We used both death records and the Fatal Encounters database to identify incidents of fatal police violence. We estimated hazard ratios (HR) using time‐varying Cox proportional hazard models stratified by census tract, controlling for age, race/ethnicity, educational attainment, health insurance type, parity, and the year and season of conception. We further stratified by race/ethnicity and infant sex to evaluate whether there were differential effects by these characteristics. Results: Exposure to an incident of fatal police violence was associated with a small increase in the hazard of late preterm birth using both the death records (N = 376, 029; hazard ratio [HR] 1.05, 95% confidence interval [CI] 1.00, 1.10) and the Fatal Encounters data (N = 938, 814; HR 1.03, 95% CI 1.00, 1.06). We also observed an association for moderate preterm birth in the Fatal Encounters data (HR 1.06, 95% CI 0.98, 1.15). We did not observe associations for early or extremely preterm birth in either data source. Larger relative hazards of moderate (HR 1.25, 95% CI 0.93, 1.68) and late preterm delivery (HR 1.18, 95% CI 1.05, 1.33) were observed among Black birth parents with female births in the Fatal Encounters data. Conclusions: Preventing police use of lethal force may reduce preterm delivery in communities where such violence occurs.